Proteases and microwave treatment on the quality of chitin and chitosan produced from white shrimp (Penaeus vannamei). Issue 2 (23rd February 2023) - Dong, Qiqi; Qiu, Weiqiang; Feng, Yuhui; Jin, Yingshan; Deng, Shanggui; Tao, Ningping; Jin, Yinzhe
Abstract: The aim of this study was to extract chitin and chitosan from shrimp shells by neutral protease‐assisted microwave multiple heating (one, two, three, and four) treatment. The structure and physicochemical properties of chitosan were characterized by scanning electron microscopy (SEM) and Fourier infrared spectroscopy (FTIR). The dielectric properties of chitosan acetate solution were determined by using a PNA‐L network analyzer, and the correlation between chitosan deacetylation degree and dielectric loss was further analyzed. The results show that the degree of deacetylation of chitosan increased from 84.9% to 90.8% with the increase in the number of microwave heating treatments. Furthermore, the chitosan prepared by multiple microwave heating was smoother. The dielectric constant of chitosan solution gradually decreases with the increase of frequency, and the dielectric loss first decreases and then increases. In addition, the dielectric loss of the chitosan solution increased with the degree of deacetylation of chitosan at 2450 MHz ( R 2  > 0.99). Therefore, enzyme‐assisted microwave extraction of chitosan can be used to obtain high‐quality chitosan under the condition of increasing the number of heating treatments. Abstract : Enzyme‐assisted microwave extraction of chitosan can be used to obtain high‐quality chitosan under the condition of increasing the number of heating treatments.